2005
DOI: 10.1111/j.1467-7687.2005.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the distributional input? A developmental investigation of asymmetry in infants’ categorization of cats and dogs

Abstract: Two experiments are reported using a visual familiarization categorization procedure. In both experiments, infants were familiarized with sets of stimuli previously shown to contain asymmetric feature distributions that support an asymmetry in young infants' categorization of cats and dogs (i.e. infants' cat category excludes dogs but their dog category includes cats). In Experiment 1, the asymmetry was replicated in 4-month-old infants. In contrast, 10-month-old infants demonstrated exclusive category represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
12
1
1
Order By: Relevance
“…Several previous studies in which infants were familiarized with multiple images of dogs and cats have shown failures to decrease looking in a nearly identical procedure, and yet had robust novelty preferences when tested on their category formation (Furrer & Younger, 2005; Quinn, 2004; Quinn & Eimas, 1996). One benefit of the procedure used here is that novelty preference is not dependent on habituation of looking to a familiar stimulus, and requiring habituation may actually underestimate infants’ memory abilities (Fagan, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies in which infants were familiarized with multiple images of dogs and cats have shown failures to decrease looking in a nearly identical procedure, and yet had robust novelty preferences when tested on their category formation (Furrer & Younger, 2005; Quinn, 2004; Quinn & Eimas, 1996). One benefit of the procedure used here is that novelty preference is not dependent on habituation of looking to a familiar stimulus, and requiring habituation may actually underestimate infants’ memory abilities (Fagan, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Categorization is inferred by their pattern of novelty preference. Studies using this approach have revealed that young infants are sensitive to adult-defined categories such as cat and dog (Furrer & Younger, 2005; Oakes & Ribar, 2005; Quinn, Eimas, & Rosenkrantz, 1993) and form prototypes of items presented during familiarization (Younger, 1985). Moreover, this response to the novel category has been observed in studies using familiarization even when infants’ looking time did not decrease over familiarization with multiple items from within a category (Furrer & Younger, 2005; Quinn, 2004; Quinn & Eimas, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work examining infants' ability to form naturally occurring categories has found that differences in within-category variability produce asymmetric behavior in habituation tasks (Quinn, Eimas, & Rosenkrantz, 1993; see also Furrer & Younger, 2006;Mareschal, French, & Quinn, 2000). When habituated to a category with low variability, infants form a narrow category and dishabituate to exemplars from a different but similar category.…”
Section: Studymentioning
confidence: 97%
“…An expanding literature in this regard is evident in consumer research (Ozanne, Brucks, & Grewal, 1992;Reutskaja, Nagel, Camerer, & Rangel, 2011), humanÁcomputer interface (Cheng & Liu, 2011;Pan et al, 2004) as well as the combination of the two, i.e., online marketing (Djamasbi, Siegel, Skorinko, & Tullis, 2011;Dreze & Hussherr, 2003). As far as we know, such a bias for less typical objects in a display has only been shown by the novelty and familiarity effects that occur during infant preference paradigms (Furrer & Younger, 2005;Oakes & Riber, 2005;Quinn, 2004;Quinn & Bhatt, 1998). The informationÁfixation link presented here is applicable to any circumstance where manipulation of gaze might be useful.…”
Section: Discussionmentioning
confidence: 99%